Unusual presentation of peripancreatic abscess associated with streptococcus anginosus and colonic diverticulosis - Berevoescu, Nicolae-Iustin; Bordea, Adrian; Berevoescu, Mihaela; Cristian, Daniel-Alin (International Surgery Journal, 2019)
Pancreatic abscesses are rare and usually occur as a pancreatitis complication. The absence of acute pancreatitis and the clinical presentation that mimics a neoplasm are very unexpected. A 49-year-old man, known with arterial hypertension and chronic infection with virus hepatitis B came to the hospital for weight loss, marked asthenia, nausea/vomiting and jaundice, associated with mild pain in the upper abdomen. At admission, without fever and no medical history of acute pancreatitis. Laboratory values showed an important inflammatory syndrome, near normal pancreatic enzymes and increased tumour markers. Abdominal computed tomography (CT) revealed a heterogeneous fluid collection with gas bubbles inside, localized into the lesser sac that tended to extend peri splenic, towards the anterior and posterior pararenal spaces and the pelvis. Surgery has led to evacuation of peripancreatic and left retrocolic abscesses, associated with debridement and peritoneal drainage. The culture yielded Streptococcus Anginosus. At 7 days post-intervention hemoperitoneum occurred and was required a second intervention for haemostasis. Subsequent favourable clinical and biological evolution, with patient discharge from the clinic 16 days after admission. Repeated CT scans of the abdomen showed resolution of lesions and at colonoscopy it was observed uncomplicated colonic diverticulosis. In this case is highlighted a rare presentation of a peripancreatic pyogenic abscess caused by Streptococcus anginosus, associated with colonic diverticulosis.